Salinization mechanisms of a small alluvial aquifer in the semiarid region of northeast Brazil - João R. F. de Almeida; Horst Frischkorn (Revista Brasileira de Engenharia Agrícola e Ambiental)
The objective of this research was to identify and quantify the primary processes responsible for the increase in salinity observed in the alluvial aquifer during the dry season. Multivariate statistical analysis and inverse geochemical modeling were used to simulate possible salinization mechanisms in the alluvial aquifer. For this, by quantifying electrical conductivity and the concentrations of the ions Ca2+, Mg2+, Na+, K+, Cl-, HCO3- and SO42- in waters from the crystalline basement near the study area, water reservoirs near the alluvial aquifer and the studied alluvial aquifer, groups were formed and discriminant analysis was applied. Significance tests showed that direct evaporation has not only an influence on the alluvial aquifer, but also a mean volumetric contribution of 15.8% from waters of the crystalline basement, accompanied by processes of salt dissolution and precipitation, which would also justify the increase in salinity observed in the alluvial aquifer in the dry period.